Optimalisasi Creative Writing Dalam Penyusunan Konten Edukatif Produk Stationery Untuk Meningkatkan Brand Awareness - Angelina Astrid Pramesty; Alfiandi Imam Mawardi (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2026)
This study aims to analyze the optimization of creative writing in developing educational stationery product content on the TikTok platform as a strategy to improve brand awareness at PT. Sarana Global Bersama. This research employed a descriptive qualitative method using a case study approach during an internship program. Data were collected through observation, documentation, and direct involvement in the planning, development, and publication of TikTok content. The findings indicate that implementing creative writing through persuasive, informative, and communicative language produces engaging content that is easy for the target audience to understand. The educational content not only introduces the advantages of stationery products but also provides information about their functions, benefits, and proper use. This strategy contributes to increasing content attractiveness, strengthening brand identity, and enhancing PT. Sarana Global Bersama’s brand awareness through the TikTok platform